ANALISIS MODEL PREDIKSI KERUSAKAN PADA PERKERASAN KAKU DENGAN METODE MEKANIS-EMPIRIS (Studi Kasus Jalan Lingkar Selatan Kota Yogyakarta ) - , SETIAWAN WIBOWO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
There are several methods to design thick layers of pavement, i.e. empirical, mechanistic-empirical and mechanistu method. Empirical approach is employed in pavement thickness design fundamentally through experimental results or experience. Meanwhile, mechanistic approach is used to find an explanation of phenomena only by investigating physical causes. Moreover, the use of mechanistic-empirical method in Indonesia is not commonly used in planning a thick layer design. The general methods used in Indonesia are AASHTO 1986 and 1993, as well as other empirical methods. This study aims to determine the required data input in the planning process of pavement design with mechanistic-empirical method